Pelatihan dan Sosialisasi Kesadaran Limbah Fast Fashion pada Santri Madrasa Mahasiswa Muamalat Yogyakarta: Indonesia - Rohma, Masitoh Nur; Priyansyah, Ahmad; Irmawati, Feni; Maghfiroh, Maghfiroh; Nihaya, Silvia Munna (UII, 2024)
Based on United Nations data, the fashion industry contributes as much as 10% to total global emissions. This condition negatively contributes to climate change, especially when associated with Sustainable Development Goals (SDGs) Point 13, climate action. In response to this condition, the community service team from the Department of International Relations, Universitas Islam Indonesia, strives to open opportunities for the implementation of SDGs Point 13 at the Madrasa Mahasiswa Muamalat, Yogyakarta. The method of activity is carried out face-to-face by conducting socialization and providing training to the santri. The first session was a socialization of